Once versus twice daily direct oral anticoagulants in patients with recent stroke and atrial fibrillation. (September 2022) - Polymeris, Alexandros A; Zietz, Annaelle; Schaub, Fabian; Meya, Louisa; Traenka, Christopher; Thilemann, Sebastian; Wagner, Benjamin; Hert, Lisa; Altersberger, Valerian L; Seiffge, David J; Lyrer, Flurina; Dittrich, Tolga; et al.
Background: Data on the safety and effectiveness of once-daily (QD) versus twice-daily (BID) direct oral anticoagulants (DOAC) in comparison to vitamin K antagonists (VKA) and to one another in patients with atrial fibrillation (AF) and recent stroke are scarce. Patients and methods: Based on prospectively obtained data from the observational registry Novel-Oral-Anticoagulants-in-Ischemic-Stroke-Patients(NOACISP)-LONGTERM (NCT03826927) from Basel, Switzerland, we compared the occurrence of the primary outcome – the composite of recurrent ischemic stroke, major bleeding, and all-cause death – among consecutive AF patients treated with either VKA, QD DOAC, or BID DOAC following a recent stroke using Cox proportional hazards regression including adjustment for potential confounders. Results: We analyzed 956 patients (median age 80 years, 46% female), of whom 128 received VKA (13.4%), 264 QD DOAC (27.6%), and 564 BID DOAC (59%). Over a total follow-up of 1596 patient-years, both QD DOAC and BID DOAC showed a lower hazard for the composite outcome compared to VKA (adjusted HR [95% CI] 0.69 [0.48, 1.01] and 0.66 [0.47, 0.91], respectively). Upon direct comparison, the hazard for the composite outcome did not differ between patients treated with QD versus BID DOAC (adjusted HR [95% CI] 0.94 [0.70, 1.26]). Secondary analyses focusing on the individual components of the composite outcome revealed no clear differences in the risk-benefit profile of QD versus BID DOAC. Discussion and conclusion: The overall benefit of DOAC over VKA seems to apply to both QD and BID DOAC in AF patients with a recent stroke, without clear evidence that one DOAC dosing regimen is more advantageous than the other.